Assessment of 2021 surveillance system for under-five children with pneumonia in Bantul Regency, Indonesia - Nining Puji Lestari; Vicka Oktaria; Samsu Aryanto; Bayu Satria Wiratama (Clinical Epidemiology and Global Health)
Introduction: Hospital involvement in pneumonia surveillance for children under five was found to be limited. This study aimed to assess the sensitivity of pneumonia surveillance using the capture-recapture method and provide an overview of pneumonia morbidity and mortality in children under five. Methods: A descriptive study using secondary data on pneumonia cases among children under five in 2021 was conducted. Data were collected from all public health centers and eight selected hospitals in Bantul Regency, chosen based on the highest number of reported cases. The sample size included all identified cases from these facilities. Cases were defined as acute pneumonia in children under five, meeting ICD-10 criteria (J12, J13, J14, J15, J16, J17, J18, and P23.9). Data were analyzed descriptively. Results: Hospitals accounted for 87.9 % (872 cases) of the 992 cases identified from both data sources. The sensitivity of surveillance systems was 2.9 % at public health centers, 21.7 % at hospitals, and 23.9 % when considering data from both sources. Furthermore, 85.7 % (n = 14) of the deaths were attributed to unspecified congenital pneumonia. Conclusions: The sensitivity of under-five pneumonia surveillance in Bantul remains low, primarily due to limited hospital participation. Strengthening hospital engagement in surveillance activities and enhancing interventions for congenital pneumonia is essential for improving case detection and public health response.